Self- consciousness in relation to moral emotions, and judgment - Strus, Włodzimierz; Ślaski, Sławomir (Studia Psychologica: Theoria et praxis, 2007)
The aim of this paper is to consider the relationship between self-consciousness and two dimensions of moral functioning: emotions and reasoning. The theory of self-consciousness by Z. Zaborowski, H. Lewis’s conceptualization of shame and guilt developed by J. Tangney and L. Kohlberg’s theory of moral reasoning development with J. Rest’s modifications was the theoretical foundation of the research. In order to measure forms of self-consciousness (external, defensive, individual and reflective) Zaborowski’s and Oleszkewicz’s Selfconsciousness Scale was used. Polish version of Test of Self-Conscious Affect-3 constructed by J. Tangney was used to measure shame-proneness and guilt-proneness. The level of moral judgment development was assessed by polish version of J. Rest’s Defining Issues Test. The research group consisted of 80 students (57 women and 23 men). Results strongly support the hypothesized link between reflective self-consciousness and guilt-proneness. Defensive selfconsciousness was positively related to shame-proneness. We have also found correlation between external form of self-consciousness and guilt proneness, as well as the relationship of individual self-consciousness to shame-proneness. In contrast results of the study shows only modest correlations between forms of self-consciousness and level’s of moral judgment rates.